Fluorescein angiography of retinal vascular involution after intravitreal injection of ranibizumab for retinopathy of prematurity - Yong Cheng; Tie-Gang Liu; Wei-Yi Li; Ming-Wei Zhao; Jian-Hong Liang (International Journal of Ophthalmology, 2019)
AIM: To describe the involution patterns of vessel growth of retina through fluorescein angiography (FA) of children, who had been under treatment up to 1y previously intravitreal ranibizumab (IVR) as monotherapy for retinopathy of prematurity (ROP). METHODS: This is a retrospective study. The medical information and FA of 17 children (34 eyes) whose area of avascular retina from the ora serrata was more than two disc diameters (DD) were analyzed. RESULTS: Among 34 eyes, all were the presence of finger-shaped vessels and arteriolar-venular shunts (100%, 34/34 eyes). Popcorn abnormalities were found in most of the eyes (94.1%, 32/34 eyes). Furthermore, in many cases (23.5%, 8/34 eyes), there were leakage persisting in the region of the junction between avascular and vascular retina. In contrast, just 2 eyes (5.9%) showed damage of retinal capillary bed and 3 eyes (8.8%) showed large area of retinal pigment epithelium (RPE) atrophy. CONCLUSION: Although IVR can be very effective in ROP, we should remain cautious as infants may remain avascular peripheral retinas and abnormal vessel. FA allows accurate visualization of vessel abnormalities in eyes with ROP, which will be helpful to affect assessment of disease activity and therapeutic effect.